High-speed obstacle avoidance for mobile robots - Borenstein, J.; Koren, Y. (Proceedings IEEE International Symposium on Intelligent Control 1988, 1988)
A real-time obstacle avoidance approach for mobile robots has been developed and implemented. This approach permits the detection of unknown obstacles simultaneously with the steering of the mobile robot to avoid collisions and the advance of the robot toward the target. The approach, called the virtual force field technique, integrates two known concepts: certainty grids for obstacle representation and potential fields for navigation. This combination is especially suitable for the accommodation of inaccurate sensor data (such as those produced by ultrasonic sensors) as well as for sensor fusion, and it allows continuous motion of the robot without stopping in front of obstacles. Experimental results from a mobile robot running at a maximum speed of 0.78 m/s demonstrate the power of the proposed algorithm.< >